2021
DOI: 10.7554/elife.69746
|View full text |Cite
|
Sign up to set email alerts
|

Convergent, functionally independent signaling by mu and delta opioid receptors in hippocampal parvalbumin interneurons

Abstract: Functional interactions between G protein-coupled receptors are poised to enhance neuronal sensitivity to neuromodulators and therapeutic drugs. Mu and Delta opioid receptors (MORs and DORs) can interact when overexpressed in the same cells, but whether co-expression of endogenous MORs and DORs in neurons leads to functional interactions is unclear. Here, in mice, we show that both MORs and DORs inhibit parvalbumin-expressing basket cells (PV-BCs) in hippocampal CA1 through partially occlusive signaling pathwa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 77 publications
(115 reference statements)
1
32
1
Order By: Relevance
“…MOR is not the only receptor mediating presynaptic neuromodulation by opioids. DOR is another well-known example that mediates Gi-coupled inhibition of neurotransmitter release in response to opioids ( Bardoni et al, 2014 ; He et al, 2021 ; Piskorowski and Chevaleyre, 2013 ). Physiological tolerance to DOR-mediated effects is well established ( DiCello et al, 2019 ; Pradhan et al, 2010 ), and agonist-induced internalization of DOR has been clearly demonstrated in the soma and dendrites of neurons ( Pradhan et al, 2009 ; Scherrer et al, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…MOR is not the only receptor mediating presynaptic neuromodulation by opioids. DOR is another well-known example that mediates Gi-coupled inhibition of neurotransmitter release in response to opioids ( Bardoni et al, 2014 ; He et al, 2021 ; Piskorowski and Chevaleyre, 2013 ). Physiological tolerance to DOR-mediated effects is well established ( DiCello et al, 2019 ; Pradhan et al, 2010 ), and agonist-induced internalization of DOR has been clearly demonstrated in the soma and dendrites of neurons ( Pradhan et al, 2009 ; Scherrer et al, 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…Physiological tolerance to DOR-mediated effects is well established ( DiCello et al, 2019 ; Pradhan et al, 2010 ), and agonist-induced internalization of DOR has been clearly demonstrated in the soma and dendrites of neurons ( Pradhan et al, 2009 ; Scherrer et al, 2006 ). Recent evidence indicates that DOR does not rapidly desensitize at the presynapse ( He et al, 2021 ). However, DOR trafficking in axons has not been studied previously, and it is not known if longer-term tolerance develops to DOR-mediated presynaptic inhibition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DOR exhibits a higher degree of tolerance than MOR and indicates that tolerance is an homologous process MOR is not the only receptor mediating presynaptic neuromodulation by opioids. DOR is another well-known example that mediates Gi-coupled inhibition of neurotransmitter release in response to opioids (Bardoni et al, 2014;He et al, 2021;Piskorowski and Chevaleyre, 2013). Physiological tolerance to DOR-mediated effects is well established (DiCello et al, 2019;Pradhan et al, 2010), and agonist-induced internalization of DOR has been clearly demonstrated in the soma and dendrites of neurons (Pradhan et al, 2009;Scherrer et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…In support of this, one study showed that MORs inhibit FSI GABA, but not regular spiking GABA basket cell input to CA1 pyramidal neurons ( Glickfeld et al, 2008 ; Shao et al, 2020 ). However, a very recent study showed that both MORs and DORs independently activate GIRK in PV neurons as well as inhibit GABA release on to pyramidal neurons ( He et al, 2021 ). MORs hyperpolarize FSI basket cell neurons, but not regular spiking basket cell neurons.…”
Section: Hippocampusmentioning
confidence: 99%